Evaluation of Brain Injury Classifications Accuracy by Using CT scan and T2 - Star Weighted Image MRI in the Emergency Department - Khlaif Almamoori, Hadeel Zaidan; Changizi, Vahid; Zeinalkhani, Fahimeh; Nasser, Ahmed Faaz (International Journal of Innovative Research in Medical Science, 2024)
Background: While the diagnosis of traumatic brain injury (TBI) is a clinical decision, neuroimaging remains vital for guiding management on the basis of identification of intracranial pathologic conditions. CT is the mainstay of imaging of acute TBI for both initial triage and follow-up, as it is fast and accurate in detecting both primary and secondary injuries that require neurosurgical intervention, also has a limited resolution capacity in detecting non-hemorrhagic lesions and those lesions located in the posterior fossa. MRI is more sensitive for the detection of certain intracranial injuries (e.g., axonal injuries) and blood products 24-48 hours after injury, but it has limitations (e.g., speed, accessibility, sensitivity to motion, and cost). The evidence primarily supports the use of MRI when CT findings are normal and there are persistent unexplained neurologic findings or at sub-acute and chronic periods. Radiologists should understand the role and optimal imaging modality to a conventional MRI protocol with minimum sequences that reduces study time in order to be able to complete examination fast with patient. The use of examination CT and a combination of MRI protocols consisting of T1, T2, FALIR and T2* in emergency department to help with the good diagnosis of brain trauma classification treatment planning and assessing response to treatment. Objective: The role of helical CT scan and MRI T2 star weighted image to classification brain injury. Method: This project is based on cross-sectional design. The population of this study were100 patients the population of this study were patients with brain trauma that have been indicated for CT and MRI test in emergency department period of sampling which was during September 2023 to February 2024. Epidemiological data were collected at admission: age, sex, TBI mechanism, presence of m TBI, moderate and severe extra-cranial injury, post-resuscitation level of consciousness expressed by GCS and its motor subscale, and pupil examination. Findings from the admission CT scan were recorded following the Traumatic Coma Data Bank classification and MRI had been done through 72h week and 2week depending on stability of patients. questionnaire was designed and copied by the researcher. Examination had done on CT scan (Philips Multiva System 64 slice) in a supine position using a standard brain protocol, as part of the initial clinical assessment, according to the Scandinavian Guidelines for Head Injury Management. MRI examinations was performed using MRI 1. 5 T scanner (Philips MULTIVA systems) using a phase array head coil at the radiology department. The data had encoded and then entered into the statistical program (SSPS version 26). Results: A total 100 were patients with brain trauma that have been indicated for CT and MRI investigated in emergency department radiographically. The age of each study samples was normally distributed and ranged from 6 to 60, 7 to 55, and 10 to 60 years with a mean of 34. 6±17 for mild group, 30. 05±13. 7 for moderate group and 10 to 60 for sever group respectively after the inclusion and exclusion criteria, without significant differences between them (P-value= 0. 454) which reflecting the matching purpose of samples collection. All the 100 participants who completed, CT identified radiographic TBI in were true positive diagnostic accuracy (60%) while missed diagnostic were 40case. In MRI were true positive diagnostic accuracy (92%) while missed in 8 cases with the most common injuries being skull fracture, concision, intracranial hemorrhage, subdural hematoma, and subarachnoid hemorrhage, diffuse axonal injury, trauma axonal injury. Using CT as the criterion standard in mild TBI, through 24h the sensitivity (0. 7%) and Specificity (29. 6%). MRI 1 through 72h after TBI had the sensitivity (86. 7%) and Specificity (100%). MRI 2 through week after TBI had the sensitivity (6. 7%) and Specificity (43. 5%). MRI 3 through 2 weeks after TBI had the sensitivity (25. 1%) and Specificity (64. 7%). Using CT as the criterion standard in moderate TBI, after brain injury through 24h the sensitivity (54. 5%) and Specificity (33. 4%). MRI1 were sensitivity (0. 9%) and Specificity (24. 1%). MRI 2 were sensitivity (87. 3%) and Specificity (97. 8%). MRI 3 were sensitivity (0. 5%) and Specificity (33. 4%). Using CT as the criterion standard in severe TBI, after brain injury through 24h the sensitivity (100%) and Specificity (57%). MRI 1 were sensitivity (0. 8%) and Specificity (75. 2%). MRI 2 were sensitivity (0. 6%) and Specificity (30%). MRI 3 were sensitivity (100%) and Specificity (100%). Conclusion: MRI is a reasonable alternative to CT to identify radiographically evident TBI in clinically stable patients. MRI is a very sensitive technique for diagnosing DAI and ATI in moderate and severe TBI. For proper diagnosis, we recommend performing a conventional MRI in the sub-acute phase (within the first 4 weeks of the trauma) that includes at least T1, T2, FLAIR and gradient echo sequences in the different slice planes that reduces study time in order to be able to complete examination fast as soon as an MRI in patients with TBI.